LEGAL PROTECTION FOR THE LOSS OF THE PASSENGER OF ONLINE TRANSPORTATION - Pujiyono, Pujiyono; Pati, Umi Khaerah (Faculty of Law, Universitas Sebelas Maret, 2019)
Online transportation shall provide a security, comfort and safety guarantee for service users, however it is not performed in the application. Service users still havenot guaranteed their rights as consumers. In the case the consumer suffers a loss, itis remain undetermined how compensation may be granted, therefore it demandsan equal legal protection. Facing this condition, Law Number 8 of 1999 on TheConsumer Protection has not yet stipulated slear provision regarding this matter,likewise the online transportation service users and service providers are only boundin limited aspects. The research method of this reasearch is normative legal researchonly focusing on the issues raised, discussed and elaborated with applying the rulesor norms in positive law, using Statutory Approaches and Conceptual Approaches,with primary and secondary legal materials. The data collection technique used isliterature study. The analysis technique used is the deductive method. The resultsshowed that there was an legal relationship between service users and onlinetransportation service providers. Consumers have the right to get protection in theform of responsibility for information, legal responsibility for services providedand responsibility for security and comfort. However, for the losses suffered, legalprotection for losses incurred by passengers in online transportation mode is still poordue to lack of regulations and the undetermined standard regulations specifically inregulating online transportation modes.